2017
DOI: 10.1038/s41598-017-17273-6
|View full text |Cite
|
Sign up to set email alerts
|

High-hole mobility polycrystalline Ge on an insulator formed by controlling precursor atomic density for solid-phase crystallization

Abstract: High-carrier mobility semiconductors on insulators are essential for fabricating advanced thin-film transistors, allowing for three-dimensional integrated circuits or high-performance mobile terminals. We investigate the low-temperature (375–450 °C) solid-phase crystallization (SPC) of Ge on a glass substrate, focusing on the precursor conditions. The substrate temperature during the precursor deposition, T d, ranged from 50 to 200 °C. According to the atomic density of the precursor and the T d dependent SPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
124
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 41 publications
5
124
0
Order By: Relevance
“…To further improve l n , we investigated the effects of T g and t. Figure 4(a) shows that the grain size increases by lowering T g , reflecting the decrease in the nucleation frequency. 9,30 Conversely, the grain size is almost constant with respect to t. As shown in Fig. 4(b), generally, the grain size of undoped Ge decreases with increasing t. This behavior was explained as the bulk nucleation occurring in thick films while interfacial nucleation remained predominant in thin films.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…To further improve l n , we investigated the effects of T g and t. Figure 4(a) shows that the grain size increases by lowering T g , reflecting the decrease in the nucleation frequency. 9,30 Conversely, the grain size is almost constant with respect to t. As shown in Fig. 4(b), generally, the grain size of undoped Ge decreases with increasing t. This behavior was explained as the bulk nucleation occurring in thick films while interfacial nucleation remained predominant in thin films.…”
mentioning
confidence: 78%
“…29 We recently found that the atomic density of amorphous Ge (a-Ge) significantly influenced subsequent SPC. [30][31][32] By using a densified a-Ge on a GeO 2 underlayer, we fabricated a poly-Ge layer with a hole mobility of 620 cm 2 /V s, 33 which greatly exceeds that of bulk-Si (430 cm 2 /V s). These achievements initiated the prospect of the development of inversion-type poly-Ge n-MOSFETs that surpass Si-MOSFETs.…”
mentioning
confidence: 99%
See 3 more Smart Citations